E EFEKTIVITAS PIJAT BAYI TEKNIK KUNCI DAN SENAM BAYI TERHADAP PENINGKATAN NAFSU MAKAN BAYI USIA 6-12 BULAN DI KLINIK PRATAMA TANJUNG DELI TUA TAHUN 2022 - Erlina . Hayati (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
The quality of baby's growth and development needs serious attention to get good nutrition. Provision of good nutrition depends on nutrition is also influenced by food consumption. Nutrition is an environmental factor that is so important to achieve optimal growth and development and is required for growth and for the normal functioning of organs and tissues of the body. Massage as an alternative to improve health by increasing body weight due to decreased appetite. Babies who do baby gymnastics talk faster, have better appetite, sleep more soundly, and in the process of developing their movements faster than babies who don't follow gymnastics. This study aims to analyze the effectiveness of baby massage with key techniques and baby gymnastics to increase the appetite of babies aged 6-12 months at the Pratama clinic Tanjung Deli Tua in 2022.Methods: This research was conducted for 4 months. This type of research is Pre Experimental and uses a one group pretest-posttest research design. The population is infants aged 6-12 months who have decreased appetite, totaling 25 infants with a sample of 23 infants and using purposive sampling technique. Results: Data collection through questionnaires and observation. The results of data analysis with the Wilcoxon test result p-value = .003 which means that there is an effect of baby massage and baby exercise on increasing appetite.Conclusion: Baby massage combined with baby gymnastics can be applied to babies aged 6-12 months, resulting in an increase in appetite, as well as solutions to overcome these problems can improve the nutritional status of infants with weight. Keywords: Infant Massage, Baby Gymnastics, Baby Appetite